Data center ethernet : data traffic congestion control - Ang, Yu Bin (2013)
Data Centre Networks have begun to grow in sizes and utilizations. To provide quality services to users, the efficiency and reliability of the interconnected links is of great importance in running a Data centre. In ensuring that quality of service (QOS) is met, congestion control has become one of the critical topics being tackled.